Exergetic model of secondary successions for plant communities in Arid Chaco (Argentina) - Karlin, Marcos Sebastián (2013)
Fil: Karlin, Marcos Sebastián. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.